Conciliation is an alternative way to resolve conflicts "In the matter of the provisions of the Civil and Administrative Procedures Code" - Nassima CHIKH (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Conciliation is an alternative way to resolve disputes, as it dispenses with judicial litigation, and is based on allowing the parties automatically or at the request of the judge at any stage in the litigation to discuss participation in finding a consensual solution to their dispute, by waiving each of them part of their rights, and it is based on special procedures stipulated by the Algerian legislator in the Civil and Administrative Procedures Code.